SOLUBILITY ENHANCEMENT OF POORLY WATER SOLUBLE DRUGS BY VARIOUS TECHNIQUES - Minocha, Sakshi; Pahwa, Dr. Shilpa; Arora, Dr. Vandana (Journal of Biomedical and Pharmaceutical Research, 2019)
Solubility is not the ability to dissolve or thaw a substance; it may happen not only due to dissolution but also because of a chemical reaction. Solubility is the phenomenon of dissolution of solid in liquid phase to provide a homogenous system. Solubility is one of the vital factors for accomplishing desired concentration of drug in systemic circulation for pharmacological response. Low aqueous solubility is the major problem seen with formulation development of new chemical entities as well as for the generic development. With all new discovered chemical entities about 40% drugs are lipophilic and doesn’t shown therapeutic range due to their poor water solubility. Drug with poor water solubility shows slow dissolution rates, incomplete absorption and low bioavailability when taken orally. Drug solubility and bioavailability enhancement are the important in the formulation of pharmaceuticals. The Biopharmaceutics Classification System shows that Class II and IV drugs have low water solubility, poor dissolution, and low bioavailability. This review mentions different approaches used for the enhancement of the solubility of poorly water-soluble drugs that includes particle size reduction, pH adjustment, and solid dispersion. This describes the techniques of solubilizaton for the attainment of effective absorption and improved bioavailability. Keywords: Solubility, BCS classification, Bioavailability, Solid-dispersion.